Natural Law as a Normative-Ethical Framework for the Protection of Human Rights - Istimeisyah, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines natural law theory as an ethical foundation for the protection of human rights (HR). The study originates from the observation that many formally valid laws often violate fundamental human values. The purpose of this research is to emphasize that natural law provides moral legitimacy to positive law and ensures the protection of human dignity. The method used is a qualitative normative approach with literature analysis, focusing on the ideas of classical philosophers such as Thomas Aquinas, Hugo Grotius, and John Locke, as well as their relevance to modern human rights principles. The results show that natural law places human dignity as the highest moral foundation of the legal system, where human rights are inherent and not dependent on the state. In the Indonesian context, the principles of natural law are reflected in Pancasila, the 1945 Constitution, and Law No. 39 of 1999 on Human Rights. The study concludes that natural law remains a relevant and universal ethical framework guiding the creation and implementation of positive law to uphold justice and humanity.